2009
DOI: 10.1021/jp905246r
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Dependent Exciton Dynamics in J-Aggregates—When Disorder Plays a Role

Abstract: Absorption and fluorescence spectral properties of J-aggregates of core-tetrasubstituted perylene bisimide (PBI) dyes have been investigated in the temperature range from 300 to 5 K. A special feature of the present PBI J-aggregates is that, in contrast to classical J-aggregates like that of pseudoisocyanine (PIC), the chromophores are held together not only by van-der-Waals interactions but also by hydrogen bonds. The temperature dependence of the spectral band widths and the Stokes shift for PBI 1 aggregates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
60
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 47 publications
5
60
0
1
Order By: Relevance
“…In other words, long wavelength J-aggregates of O1 are probably deactivated by a radiationless pathway. A corresponding broadening by inhomogeneity of the aggregates of a sulfopropyl thiacarbocyanine has been reported previously [27]. It is noteworthy that the formation of J-and H-aggregates was not found for O2 which differs from the O1 structure mainly by the absence of an additional -CH 2 -group in the aliphatic tail of the molecule.…”
Section: Resultssupporting
confidence: 74%
“…In other words, long wavelength J-aggregates of O1 are probably deactivated by a radiationless pathway. A corresponding broadening by inhomogeneity of the aggregates of a sulfopropyl thiacarbocyanine has been reported previously [27]. It is noteworthy that the formation of J-and H-aggregates was not found for O2 which differs from the O1 structure mainly by the absence of an additional -CH 2 -group in the aliphatic tail of the molecule.…”
Section: Resultssupporting
confidence: 74%
“…Another mechanism how temperature may influence the fluorescence spectrum is by changing exciton ability to reach low energy sites of the disordered chain. These processes were investigated both experimentally and theoretically in J‐aggregates 26, 27. Because of slow exciton migration even at high temperatures, this mechanism in the composite is not important as well.…”
Section: Resultsmentioning
confidence: 99%
“…However, temperature-dependent absorption and fluorescence spectroscopic studies on exciton dynamics reveal PBI 4-1a J-aggregates have a very large level of structural disorder even at low temperature. 307 The structural disorder was related to different orientations of the four aryloxy substituents at the bay area, varying torsional angles between the two naphthalene imide subunits, and cis-and transoid hydrogen-bonding alignments. Single molecule spectroscopic studies on the highly fluorescent Jaggregate confirmed strong fluctuations of fluorescence intensity (so-called fluorescence blinking) in individual J-aggregates of 4-1a, which could be related to one-dimensional exciton transport over distances up to 70 nm in these nanomaterials.…”
Section: Self-assembly Directed By Imide−imide H-bonding Interactionsmentioning
confidence: 99%